The Effect of Mind Mapping Media toward Physics Concepts Understanding - Anafitriani Anafitriani; Baiq Azmi Sukroyanti; Lovy Herayanti (Lensa: Jurnal Kependidikan Fisika, 2019)
Science learning carried out by teachers mostly uses conventional methods and rarely uses media in the activities of their teaching and learning process. Media mind mapping in physics learning can be used to describe a lot of material and can package it to be more interesting. The aim of this research to determine the effect of mind mapping media toward the students’ concept understanding. This study used quasi-experimental research with pretest and posttest control group design. The population used was all students of class X in SMA Negeri 1 Lingsar at 2018/2019 Academic Year. The number of samples are 32 students for the experiment class and 33 students for the control class taken by purposive sampling technique. Data analysis technique used is the t-test using IBM SPSS Statistics 22. Based on the results of hypothesis testing (t test), it is known that the significance value of the posttest data (0.00) is smaller than alpha testing (0.05), so it can be stated that the mind mapping learning method influences the students' understanding of concepts.